2004 IEEE International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.2004.1326019
|View full text |Cite
|
Sign up to set email alerts
|

Automatic indexing of key sentences for lecture archives using statistics of presumed discourse markers

Abstract: Automatic extraction of key sentences from lecture audio archives is addressed. The method makes use of the characteristic expressions used in initial utterances of sections, which are defined as discourse markers and derived in a totally unsupervised manner based on word statistics. The statistics of the presumed discourse markers are then used to define the importance of the sentences. It is also combined with the conventional tf-idf measure of content words. Experimental results using a large corpus of lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Comparing the cases (2) and (3) in Table 2, it is observed that the ASR degraded accuracy, especially on the precision. In [10], however, we showed that major cause is incorrect sentence segmentation by automatic period insertion rather than word substitution errors.…”
Section: Results Of Key Sentence Indexingmentioning
confidence: 88%
See 1 more Smart Citation
“…Comparing the cases (2) and (3) in Table 2, it is observed that the ASR degraded accuracy, especially on the precision. In [10], however, we showed that major cause is incorrect sentence segmentation by automatic period insertion rather than word substitution errors.…”
Section: Results Of Key Sentence Indexingmentioning
confidence: 88%
“…It is equivalent to the orthodox speech recognition described in equation (9) when the 0/1 loss function is used in equation (10). In our baseline ASR system, this decoding is used.…”
Section: Ae´ µ Argminmentioning
confidence: 99%
“…We have proposed a method to automatically train a set of discourse markers without any manual tags, and shown the effectiveness in segmentation of lecture audio [19,5]. Then, we apply the discourse segmentation to extraction of key sentences from lectures [20,5] for generating more informative tags of the indices.…”
Section: Discourse Modeling Of Lecture Presentationsmentioning
confidence: 99%
“…Previous studies either provide very limited support for deviations from presentation script [78] or only perform off-line alignment of speech and presentation content [61,88]. Real-time tracking of presentation content is a novel approach for providing content-based assistance during presentations.…”
Section: Presentation Tracking and Potential Applicationsmentioning
confidence: 99%
“…Kawahara et al [78] extracted characteristic keywords of the lecture using tf-idf weighting and then used the extracted keywords as one of the measures for indexing key sentences in lecture archives.…”
Section: Term Weightingmentioning
confidence: 99%